The Analysis of QRIS Usage in Micro, Small, and Medium Enterprises (MSMEs) in Medan City to Encourage Digital Economy Development - Lusi Elviani Rangkuti; Wahyu Hidayatullah; Nadhila Izzati; Yovie Apryadi Lesmana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The aim of this research is to analyze the use of QRIS in MSMEs in Medan City so that they can encourage and advance MSMEs, so that they can encourage digital development. This research was conducted using descriptive qualitative, namely data that is not expressed in numerical form. Rather, the data is expressed in the form of words and sentences. With the existence of QRIS for MSMEs, digital payments can increase transaction efficiency and reduce operational costs for MSMEs. MSMEs in Medan City often lose money, which can threaten the sustainability of their business. The implementation of QRIS in Medan City has reached approximately 58.6% of users. Of the large number of users, there are still some business activities, especially MSMEs, that have not utilized the use of QRIS which can help accelerate the use and development of the digital economy. It can be concluded that the use of QRIS for MSMEs in Medan City can be an effective strategy in encouraging digital economic growth at the local level.